Altruists, Egoists, and Hooligans in a Local Interaction Model - Eshel, Ilan; Samuelson, Larry; Shaked, Avner (American Economic Review, 1998)
We study a population of agents, each of whom can be an Altruist or an Egoist. Altruism is a strictly dominated strategy. Agents choose their actions by imitating others who earn high payoffs. Interactions between agents are local, so that each agent affects (and is affected by) only his neighbors. Altruists can survive in such a world if they are grouped together, so that the benefits of altruism are enjoyed primarily by other Altruists, who then earn relatively high payoffs and are imitated. Altruists continue to survive in the presence of mutations that continually introduce Egoists into the population.